IDENTIFYING THE USE OF ABSTRACT AND CONCRETE NOUN IN CHARLOTTE'S WEB NOVEL BY E.B.WHITE - Shella Daafia (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
This research is conducted to identifying the used concrete and abstract noun in Charlotte's Web Novel by E.B White. The main focus of this research to find concrete and abstract noun from Charlotte's Web Novel. An abstract noun is a word that expresses ideas, feelings, situations that can imagine and feel but can't be touched by our senses. A concrete noun tangible word that can be seen with our senses can be touched and can be observed. The type of this research is used the descriptive qualitative method. This research was conducted by analyzing and identifying the use of concrete and abstract nouns that most often appear in Charlotte's Web novel. This research employs descriptive qualitative research. To analyze the data, the researcher uses several steps; the first is reading the novel's, the second is identifying and collecting the data, third is writing all of the data in the paper. The result of this study shows that there are 273 total numbers of abstract nouns, the most abstract nouns that appeared in this novel word "Life" there are 36 words. There is 2.799 total number of concrete nouns, the most concrete nouns that appeared in this novel word "Wilbur" as a name of a person.